2021
DOI: 10.1111/pce.14196
|View full text |Cite
|
Sign up to set email alerts
|

Cytosolic proline is required for basal freezing tolerance in Arabidopsis

Abstract: The amino acid proline accumulates in many plant species under abiotic stress conditions, and various protective functions have been proposed. During cold stress, however, proline content in Arabidopsis thaliana does not correlate with freezing tolerance. Freezing sensitivity of a starchless plastidic phosphoglucomutase mutant (pgm) indicated that localization of proline in the cytosol might stabilize the plasma membrane during freeze–thaw events. Here, we show that re‐allocation of proline from cytosol to vac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 38 publications
(53 reference statements)
1
8
0
Order By: Relevance
“…Moreover, an earlier study on coffee genotypes with different cold sensitivities reported higher expression of sugar contents and respiratory enzyme activities [ 37 ]. Particularly, the better growth of GX74 and respective higher expressions of HKs and PGM is consistent with the earlier reports on Jatropha curcas [ 38 ] and Arabidopsis [ 39 ]. Additionally, the XYL4 gene has been previously highlighted as an important gene in abiotic stress tolerance in alfalfa [ 40 ]; thus, it may also function similarly in rapeseed.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, an earlier study on coffee genotypes with different cold sensitivities reported higher expression of sugar contents and respiratory enzyme activities [ 37 ]. Particularly, the better growth of GX74 and respective higher expressions of HKs and PGM is consistent with the earlier reports on Jatropha curcas [ 38 ] and Arabidopsis [ 39 ]. Additionally, the XYL4 gene has been previously highlighted as an important gene in abiotic stress tolerance in alfalfa [ 40 ]; thus, it may also function similarly in rapeseed.…”
Section: Discussionsupporting
confidence: 92%
“…The Sid2-1 mutant was reported in Arabidopsis, significantly increasing soluble sugars to improve drought and heat stress (Kumazaki and Suzuki, 2019). Similarly, heat stress increased proline content in leaves of soybean (Amirjani, 2010), tomato (Rivero et al, 2004), chickpea (Chakraborty and Tongden, 2005), and Arabidopsis (Zhang and Huang, 2013;Gurrieri et al, 2020;Hoermiller et al, 2022). The cluster 2 DEGs (Figure 4; Table S2) are associated with late embryogenesis abundant protein (Magwanga et al, 2018) and ubiquitin (Qian et al, 2020a), which protect sub-cellular and cellular structures from dehydration and oxidative forces.…”
Section: Discussionmentioning
confidence: 92%
“…This indicates a significant cold‐induced reprogramming of plant metabolism to stabilize a new metabolic homeostasis and to prevent irreversible tissue damage (Kosová et al, 2011). Previous studies have shown that regulation of carbon allocation and flux partitioning between compartments, for example, chloroplasts and cytosol, plays a central role in cold acclimation because it enables compartment‐specific accumulation of osmotically active and cryoprotective substances (Fürtauer et al, 2016; Hoermiller et al, 2017; Hoermiller et al, 2022; Lundmark et al, 2006). To reveal if and how deficiencies in starch and flavonoid metabolism may affect carbon partitioning during cold acclimation, substrate saturated enzyme activities, that is, v max , of the central carbohydrate metabolism were quantified at different temperatures ranging from ambient (22°C) to low (4°C) temperature.…”
Section: Discussionmentioning
confidence: 99%